Design of a screw heat exchanger as the liquid suction heat exchanger in a vapor compression refrigeration system - Antonio, Francis J. (College of Engineering, University of the Philippines Diliman, 2014)
A screw heat exchange (SHX) is a geometrically enhanced heat exchanger consisting of a rectangular helically coiled duct placed inside a cylindrical shell, designed to avoid saturated liquid formation at the compressor suction port and to increase the refrigerating effect (RE) of a vapor compression refrigeration system. The aim of this paper is to optimize SHX in terms of varying coil aspect ratio (CAR) as a liquid-suction heat exhanger (LSHE) in a vapor compression refrigeration system. CAR is the ratio of the coil duct's length to the coil duct's tube height. The optimized SHX was compared to a commercially available LSHE with the same length and same mass flow rate and its corresponding refrigeration system to an equivalent standard vapor compression cycle (VCC) in terms of refrigerating effect (RE) and coefficient of performance (COP). Also, the varying CAR of SHX was used to establish relationship in its degrees of subcool and superheat, effectiveness, number of transfer units (NTU) and RE. The SHX with Square Coil Suction (SHXSCS) was also compared to the SHX with Circular Coil Section (SHXSCS) wherein the diameter of the circular coil section is the sames as the hydraulic diameter of the square coil section. Optimization of SHX was done through CFD modelling by Solidworks Flow Simulation. Validation of the simulation results was based on the experimental data from related literature. The results show that the CAR of range from 30 to 37 is suitable for LSHE. Based on optimized CAR, RE of SHX is larger by an average of 6.23% and 19.13% compared to that of tube-in-tube exchanger (TTHE) and to that of the standard VCC, respectively. The COP of the SHX is 6.61% higher than those of SHXCCS, respectively. Overall, the SHX has nominal degrees of superheat of 22.17C and nominal degrees of subcool of 17.63C.